Cross sectional study on newborn care practices in a rural area - Mani, Chandra; Lal, Prabhat Kumar; Kumar, Laxman (International Journal Of Community Medicine And Public Health, 2019)
Background: NMR contributes to two-third of infant mortality and proper newborn care is essential for achieving the target of reduction in IMR. The present study was conducted to find the newborn care practices in a rural community and to explore the associated factors. Methods: The present community based cross sectional study was conducted upon children born in the study area within past three months. Mothers were interviewed using pretested proforma. Results: It was seen that 87.3% children were cared by their mothers, rooming-in was universal, 82.1% children were kept warm, early bathing was avoided by 45.8% mothers, 96.2% of children were given vaccine at birth and umbilical stump hygiene was maintained in 61.3% cases. Conclusions: The newborn care practices are far from ideal. Community based interventions can be helpful to improve the same.